(untitled) (The Peerian Journal, 2022)
This study attempts to determine the role of educational games on learning a foreign language, and to compare games with more traditional practices as effective learning tools on the basic educational stage students at governmental Schools and institutes in Uzbekistan, an experimental research is conducted using three groups out of six randomly